2019
DOI: 10.1136/neurintsurg-2019-015129
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of preoperative endovascular embolization of meningiomas: subanalysis of anatomic location and arterial supply

Abstract: IntroductionEndovascular embolization of intracranial meningiomas is commonly used as an adjunct to surgical resection. We sought to describe the anatomic locations and vascular supplies of meningiomas to identify characteristics predictive of successful preoperative endovascular embolization.MethodsWe conducted a retrospective review of 139 meningioma cases receiving cerebral angiograms for possible preoperative endovascular embolization at our institution between December 2000 and March 2017. The extent of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…The high incidence rates and surgical difficulties for uneasily accessible locations of meningioma challenge the clinicians despite the benign nature of this tumor. As symptoms and treatment strategies largely depend on the location, it is indispensable to analyze the role of lesion location in clinical investigation of meningiomas (19,20). A visual-perceivable graphic pattern is required for identifying and visualizing tumor locations rather than complicated table analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence rates and surgical difficulties for uneasily accessible locations of meningioma challenge the clinicians despite the benign nature of this tumor. As symptoms and treatment strategies largely depend on the location, it is indispensable to analyze the role of lesion location in clinical investigation of meningiomas (19,20). A visual-perceivable graphic pattern is required for identifying and visualizing tumor locations rather than complicated table analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study has shown high rates of success for embolization of the APA. 25 It was decided that the patient should undergo a preoperative embolization to aid in surgical resection. Our case is unique in that our treatment management included the preoperative use of endovascular arterial embolization followed by surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Algunas de las recomendaciones para la embolización preoperatoria de los meningiomas, incluyen el tamaño (> 4 cm de diámetro), irrigación proveniente de la carótida externa (al menos en 50% por el fácil acceso), tumores hipervascularizados, situados en áreas elocuentes y no calcificados 6 . Otros estudios demuestran que la embolización completa de estos tumores es mayor en aquellos meningiomas localizados a nivel parasagital, en la convexidad, o con irrigación proveniente de la arteria faríngea ascendente 7 .…”
Section: Discussionunclassified